1974
DOI: 10.1002/art.1780170306
|View full text |Cite
|
Sign up to set email alerts
|

In vitro rabbit articular cartilage organ model I. Morphology and glycosaminoglycan metabolism

Abstract: A new in vitro adult articular cartilage organ model is described. Cartilage explants from adult rabbits have maintained a maximum glycosaminoglycan synthetic rate from day 7 to day 14 of incubation and normal morphology through day 10. The metabolic and histologic stability of this articular cartilage model suggests its suitability for investigating synthesis and degradation in normal, pharmacologically altered, and diseased cartilage. 27), and cell culture techniques (28-31).While providing valuable metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1974
1974
1981
1981

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The validity of 35S uptake as a viability test in the articular cartilage model used in this study was demonstrated previously whereby successive '% autoradio- graphs showed the appearance of exposed halide grains initially only over the chondrocytes, a little later over both chondrocytes and matrix, and finally only over the matrix (19).…”
Section: Discussionsupporting
confidence: 74%
“…The validity of 35S uptake as a viability test in the articular cartilage model used in this study was demonstrated previously whereby successive '% autoradio- graphs showed the appearance of exposed halide grains initially only over the chondrocytes, a little later over both chondrocytes and matrix, and finally only over the matrix (19).…”
Section: Discussionsupporting
confidence: 74%
“…Following culture, explants pulsed with labeled sulfate were dialyzed against repeated changes of distilled water for 48-72 hours, lyophilized, and alkaline hydrolyzed (23). Aliquots were: 1) directly counted as previously described (8), 2) the macro precipitability of label determined by cetyl trimethyl ammonium bromide precipitation using cold chondroitin sulfate as a carrier (8), and 3) protein content quantitated by Lowry analysis (24).…”
Section: Methodsmentioning
confidence: 99%
“…The articular cartilage model used in this study was described in a previous article (7). "Slice" and "plug" explants were removed aseptically from the distal femoral condyles of adult male New Zealand white rabbits and were cultured in MEM Eagle/ NCTC 109/10~o fetal calf serum at 37°C and saturation humidity in 5% carbon dioxide and in 1% (7.6 mm Hg), 5% (38 mm Hg), 21% (160 mm Hg), 35% (266 mm Hg), 60% (456 mm Hg) and 90% (684 mm Hg) oxygen with nitrogen making up the balance of the gas.…”
Section: Methodsmentioning
confidence: 99%
“…A 0.2-ml aliquot was realkalinized and assayed for DNA with indole (7,9). A 0.1-ml aliquot was assayed for protein (7,lO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation